Motivasi Belajar dan Prestasi Belajar Fisika Ditinjau dari Jenis Kelamin - Aloisius Harso; Juwita Merdja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to analyze the differences in learning motivation and physics learning outcomes between male and female students of class X. This research is a comparative causal research which is an ex post facto research. The population of this research is all of the tenth grade high school students in Nangapanda District as many as 220 students. The sample was determined by proportional random sampling, amounting to 80 students. Data collected in this study are students' learning motivation obtained through the provision of a learning motivation questionnaire and physics learning achievement obtained through physics learning achievement tests in the form of multiple choice questions. Data were analyzed using descriptive statistics and ANAVA. As a follow-up to ANAVA, a Least Significant Difference (LSD) was used to test the comparison of the pairs of average scores for each gender group. The results of this study indicate that there are differences in learning motivation (F = 62,139; p <0.05) and physics learning achievement (F = 11,377; p <0.05) which are significant between female and male students. Female students have higher learning motivation and physics learning achievement compared to male students. Keywords: Learning Motivation, Physics Learning Achievement, Gender